Land rehabilitation of post-mining must be done with reforestation. Reforestation success in post-mining revegetation should to refer the characteristics of natural forests. The success of the reforestation is expected to reach a climax forest ecosystem. How much time is needed to achieve the desired condition (success reforestation), in this case described as the age of achievement expectations of reforestation success to reach a climax forest ecosystem (the basalt area). The research is aim - Nining Puspaningsih; Kukuh Murtilaksono; Naik Sinukaban; I Nengah Surati Jaya; Yadi Setiadi (Forum Pasca Sarjana, 2010)
Land rehabilitation of post-mining must be done with reforestation. Reforestation success in post-mining revegetation should to refer the characteristics of natural forests. The success of the reforestation is expected to reach a climax forest ecosystem. How much time is needed to achieve the desired condition (success reforestation), in this case described as the age of achievement expectations of reforestation success to reach a climax forest ecosystem (the basalt area). The research is aimed to predict reforestation success age. The study used regression analysis for determining the reforestation success age in mining area. The measure used to determining the reforestation success age is basalt area (LBDS) of natural forests. Mathematically it can be summarized to LBDS = f (age). The study found the age of achievement expectations of reforestation success is 75 years. Over the 75 years when the efforts to improve, protect and enhance forest functions are be done well, consistently, and even continued to rise, certainly reforestation success will be achieved, or even faster. Key words: rehabilitation, mining area, reforestation, basalt area, reforestation success age